The state of physical and psychological components of health in the quality of life of the university students - Tsos, Anatolii V.; Homych, Anatolii; Sabirov, Oleksandr; Цьось, Анатолій Васильович; Хомич, Анатолій; Сабіров, Олександр (Państwowa Szkoła Wyższa im. Papieża Jana Pawła II w Białej Podlaskiej, 2013)
The article presents a state of physical and mental health components of quality of life of university students. The results indicate that the physical component of student’s health is within 51.12, psychological - 44,27 points. The level of physical and mental health components of quality of student’s life in Ukraine, Belarus and Russia do not differ significantly. It is statistically proved that correlation relationship between role-functioning caused by physical condition and role functioning, emotional state caused by the students’ overall health and vitality, general health and mental health, social functioning and role functioning caused by emotional state, social functioning and mental health.
Keywords: health; quality of life; students; physical and psychological components of health